Selected longitudinal results for OnLAC years 10, 11 & 12 for a sample of 1714 young people in care aged 10-15 in year 10 - Flynn, Robert; Miller, Meagan (Université d'Ottawa | University of Ottawa, 2013)
Presented at the 2013 Ontario Looking After Children Data Review Day
Keywords: ontario looking after children; onlac; child welfare; longitudinal; outcome monitoring